Початки формування збірок військово-історичних пам’яток музеями Львова (друга половина XIX – початок XX ст.) - Петрик, Н. Р. (Видавництво Львівської політехніки, 2014)
Досліджено початковий період накопичення військово-історичних пам’яток у львівських музейних колекціях другої половини XIX – на початку XX ст. Розкрито внесок у музейне будівництво громадських та культурних інституцій та окремих діячів. Описано процес становлення головних музейних установ польської громади та формування їхніх військово-історичних колекцій, провідне значення серед яких відігравав Музей імені князів Любомирських, а з 1908 року – Національний Музей імені короля Яна ІІІ. The beginning of accumulation of military and historical attractions in a museum collections of Lviv from the second half of XIX until beginning of the XX century and a process of creating military and historical museums has been investigated in this article. A contribution of the public and cultural institutions and any public and scientific figures in the museum construction has been revealed. The national factor was one of the most important in a public life of Lviv at that time. Polish and Ukrainian communities strived to create their own independent states. Their desires were represented in a museum construction. From the second half of XIX century Polish community began the formation of museum collections. First military and historical attractions were concentrated in that collections. One of the first exhibition, where military and historical attractions were exhibited, was organized by National Institution named by Ossolinski in Lviv in 1861. Later public museums began to appeared in Lviv National Museum of King Jan III was the top museum institution of Polish community in Lviv. This Museum had one of the largest collection of military historical attractions. Besides, there were large military and historical collections from a Museum of the Princes Lubomyrski and Boleslaw Ozhehovych collection. All these museum institutions and collections belongs to the Polish cultural society. The main figure in process of museum formation was Alexander Cholovscy. During the World War II collections of Lviv museums had suffered losses. A large part of the military and historical collections were destroyed; another one was moved abroad. Lviv museums were reorganized. That’s why, in 1940 all military and historical attractions, that were saved, have been focused in the new Lviv Historical Museum. Nowadays collections of Lviv museums from the second half of the XIX century are the most important sources for learning the military history of Ukrainian and Polish nations.
Keywords: музейні колекції; польська громада; Музей імені князів Любомирських; museum collections; Polish and Ukrainian communities; Museum of the Princes Lubomyrski